An analysis of the information technology outsourcing domain: A social network and Triple helix approach. Issue 11 (23rd August 2013) - Swar, Bobby; Khan, Gohar Feroz
<x xml:space="preserve">Abstract</x> Information technology (IT) outsourcing has become a widely accepted management strategy. As a consequence, a great deal of research on the IT outsourcing domain, covering a wide range of issues, has been conducted. This study investigates the IT outsourcing knowledge infrastructure from a network point of view. Triple helix indicators and social network analysis techniques are employed on 288 scholarly papers obtained from the Web of Science database using keywords related to IT outsourcing. The results reveal the key players in IT outsourcing research collaborations; their network characteristics, such as degree centrality; and the relationship of academia, industry, and government in terms of IT outsourcing knowledge production. This article also provides results‐based implications.